The experience of under-screened and never-screened participants using clinician-supported self-collection cervical screening within the Australian National Cervical Screening Program. (February 2022) - Creagh, Nicola S; Zammit, Claire; Brotherton, Julia ML; Saville, Marion; McDermott, Tracey; Nightingale, Claire; Kelaher, Margaret
Background: Australia has had significant successes in the prevention of cervical cancer. However, there is considerable scope for improving screening participation. In December 2017, Australia shifted from cytology to a human papillomavirus–based screening program as part of the renewed National Cervical Screening Program. This provided the opportunity to introduce a clinician-supported self-collection cervical screening pathway, which allows screening participants aged 30 years or more and who are under-screened or never-screened to screen via a self-collected human papillomavirus test. Objective: This study aimed to explore screening participant experiences of a clinician-supported self-collection cervical screening pathway. Methods: Interviews (n = 45) were conducted with participants who had used the clinician-supported self-collection cervical screening pathway in the Australian National Cervical Screening Program between December 2017 and April 2019. Interviews were analyzed using template analysis. Results: Under-screened and never-screened participants reported a variety of interrelated barriers to cervical screening due to the nature of the test. For these participants, self-collection was a preferable way to perform screening as it overcame various barriers, was easy to use and promoted a sense of empowerment. Participants reported that the role of their practitioner was influential in their decision to undertake cervical screening, and that the support and information provided was a key factor in their experiences of the self-collection pathway. Conclusion: Findings support the use of a clinician-supported model of care, as an alternative screening modality in Australia's National Cervical Screening Program. As more countries consider the move from a cytology to human papillomavirus–based cervical screening program, this model may assist in greater engagement of under-screened participants.